PENINGKATAN HASIL BELAJAR PERPANGKATAN DAN AKAR SEDERHANA MELALUI PENERAPAN ALAT PERAGA ‘PAPER DAN NOKRUMTUL’ PADA PESERTA DIDIK KELAS V DI SD NEGERI 2 BENGKULU SELATAN - Zarlan Saryadi (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2018)
The purpose of this classroom action research is to: (1) describe mathematics learning in simple matter of powers and roots in grade V elementary school students of State 2 South Bengkulu by applying 'Paper and Nokrumtul' props; and (2) to describe the effectiveness of the Implementation of 'Paper and Nokrumtul' Toolkit on Improving Learning Outcomes of Simple Departments and Roots to Grade V Students in elementary school students of State 2 South Bengkulu. The location of this class action research activity is at elementary school State number 2 South Bengkulu. Students who are the subject of this study are students in class V with the number of 20 people consisting of 12 men of gender and 8 others came from the female sex, all students as subjects of this study will be subject to action in accordance with the flow real learning. From the results of learning activities that have been done for two cycles, and based on all the discussion and analysis that has been done can be concluded that the learning by applying the props